1990
DOI: 10.1111/j.1469-8137.1990.tb00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of colonization and sporulation by VA mycorrhizal fungi to plant nutrient and carbohydrate contents*

Abstract: SUMMARYVesicular-arbuscular (VA) mycorrhizal fungi typically produce spores either within roots of a host plant or in the soil. Experiments were conducted to examine the effects of plant nutrition, as measured by tissue N, P, K, and soluble sugar concentrations, upon colonization of roots of Paspalum notatum Flugge and sporulation within roots by Glomus intraradix Schenck & Smith and in the soil by Acaulospora longula Spain & Schenck and Gigaspora margarita Becker & Hall. Plants receiving a balanced nutrient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 28 publications
5
49
0
2
Order By: Relevance
“…One of the factors contributing to this result was probably the low concentration of P in this nutrient solution (3 μM). High concentration of P can reduce hyphal growth (23), as well as colonization and sporulation of AMF (10), while the reduction can improve spore production (9,38). On the other side, high sporulation of G. etunicatum was obtained in substrate irrigated with S1B or with S3, what indicates possible plasticity of this isolate in relation to wide values of pH and P concentration in the nutrient solution.…”
Section: Discussionmentioning
confidence: 93%
“…One of the factors contributing to this result was probably the low concentration of P in this nutrient solution (3 μM). High concentration of P can reduce hyphal growth (23), as well as colonization and sporulation of AMF (10), while the reduction can improve spore production (9,38). On the other side, high sporulation of G. etunicatum was obtained in substrate irrigated with S1B or with S3, what indicates possible plasticity of this isolate in relation to wide values of pH and P concentration in the nutrient solution.…”
Section: Discussionmentioning
confidence: 93%
“…Clapp et al (1995), using molecular techniques, demonstrated a positive relationship between the distribution of spores and root colonization in Acaulospora and Scutellospora species under field conditions. More detailed works, carried out under controlled conditions, suggest that the production of spores is related more strongly to the length of root colonization than to the percent root colonization (Douds & Schenck 1990, Gazey et al 1992. Other papers showed that plants with finer roots favoured the sporulation of AMF (Kormanick et al 1980), and yet others correlated the increased number of spores with the improved nutritional state of the plants (Louis & Lim 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Because mycorrhizae help to increase uptake of minerals in plants, the levels of P and Zn in the plant may regulate root colonization and spore formation (Smith and Read, 1997). It has been shown that high levels of phosphorus in soil and plant are able to inhibit mycorrhiza formation (Douds and Schenck, 1990) and influence the diversity of AM fungi in field soils (Cuenca and Menses, 1996).…”
Section: Discussionmentioning
confidence: 99%